2011
DOI: 10.1093/nar/gkr124
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic restriction activity by apolipoprotein B mRNA editing enzyme APOBEC1 against the mobility of autonomous retrotransposons

Abstract: The ability of mammalian cytidine deaminases encoded by the APOBEC3 (A3) genes to restrict a broad number of endogenous retroelements and exogenous retroviruses, including murine leukemia virus and human immunodeficiency virus (HIV)-1, is now well established. The RNA editing family member apolipoprotein B (apo B)-editing catalytic subunit 1 (APOBEC1; A1) from a variety of mammalian species, a protein involved in lipid transport and which mediates C–U deamination of mRNA for apo B, has also been shown to modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 98 publications
(136 reference statements)
7
103
0
1
Order By: Relevance
“…A1 as well as hA3A and hA3G are able to inhibit nascent L1 DNA accumulation, suggesting interference with L1 reverse transcription, integration and/or intracellular movement of L1 ribonucleoprotein particles (RNPs). 14,19 Furthermore, the suppressive activity against de novo L1 DNA synthesis was mainly in a deaminationindependent manner, and was not affected by subcellular localization of the proteins. 14 AID/APOBEC proteins might be able to interact with the cytoplasmic RNPs and interfere with subsequent RNPs transport and/or nuclear import.…”
Section: Aid/apobec Deaminases As Restriction Factors Of Endogenous Rmentioning
confidence: 93%
See 3 more Smart Citations
“…A1 as well as hA3A and hA3G are able to inhibit nascent L1 DNA accumulation, suggesting interference with L1 reverse transcription, integration and/or intracellular movement of L1 ribonucleoprotein particles (RNPs). 14,19 Furthermore, the suppressive activity against de novo L1 DNA synthesis was mainly in a deaminationindependent manner, and was not affected by subcellular localization of the proteins. 14 AID/APOBEC proteins might be able to interact with the cytoplasmic RNPs and interfere with subsequent RNPs transport and/or nuclear import.…”
Section: Aid/apobec Deaminases As Restriction Factors Of Endogenous Rmentioning
confidence: 93%
“…[12][13][14] In addition, several reports indicated that A1s from several mammalian species inhibit a wide range of exogenous retroviruses such as HIV-1. [15][16][17][18] These results raise the possibility that not only A3 proteins but also AID and A1 cytidine deaminases are likely to participate in the intrinsic immunity in various mammalian species against the retrotransposition of endogenous and exogenous retroviruses.…”
Section: Aid/apobec Deaminases As Restriction Factors Of Non-ltr Retrmentioning
confidence: 99%
See 2 more Smart Citations
“…Several human APOBEC3 genes (128-133), but not mouse mA3 (129,134), inhibit L1 retrotransposition in vitro. Similarly, the overexpression of APOBEC1 or AID from human, rat and mouse can inhibit the retrotransposition activity of a cloned human L1 in human cell lines (135,136). It is puzzling, however, that L1 inhibition by all these deaminase appears to be independent of their deaminase activity.…”
Section: Host Factors For Posttranscriptional Regulation-several Cytimentioning
confidence: 99%